The social construction of free trade: the European Union, NAFTA, and MERCOSUR. - Duina, Francesco; Duina, Francesco (Princeton University Press, 2013)
This book offers a compelling new interpretation of the proliferation of regional trade agreements (RTAs) at the end of the twentieth century. Challenging the widespread assumption that RTAs should be seen as fundamentally similar economic initiatives to pursue free trade, Francesco Duina proposes that the world is reorganizing itself into regions that are highly distinctive and enduring. With evidence from Europe, North America, and South America, he challenges our understanding of globalization, the nature of markets, and the spread of neoliberalism. The pursuit of free trade is a profoundly social process and, as such, a unique endeavor wherever it takes place. In an unprecedented comparative analysis, the book offers striking evidence of differences in the legal architectures erected to standardize the worldview of market participants and the reaction of key societal organizations--interest groups, businesses, and national administrations--to a broader marketplace. The author gives special attention to developments in three key areas of economic life: women in the workplace, the dairy industry, and labor rights. With its bold and original approach and its impressive range of data,The Social Construction of Free Traderepresents a major advance in the growing fields of economic sociology and comparative regional integration.